The Relationship Between the Smoking Duration of E-Cigarette and Blood Pressure in the Udanawu Vapor Community, Blitar - Ibnu Muhariawan Restuaji; Refi Anjarsari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
The use of e-cigarettes is increasing in the community and is suspected to be associated with changes in blood pressure due to nicotine exposure. This study aims to determine the relationship between the duration of e-cigarette use and blood pressure in men aged 20–30 years in the e-cigarette user community in Udanawu, Blitar. This is an analytical observational study with a cross-sectional design involving 17 respondents selected through purposive sampling. Blood pressure data were measured with a sphygmomanometer and analyzed using the Spearman correlation test. The results showed that the average systolic blood pressure of respondents was 117.65 mmHg, and the average diastolic blood pressure was 87.65 mmHg. Statistical analysis showed a significant relationship between the duration of e-cigarette use and systolic blood pressure (p=0.003; r=0.679) and diastolic blood pressure (p=0.005; r=0.646). These results indicate that the longer the e-cigarette use, the greater the tendency for blood pressure to increase in respondents. Thus, long-term use of e-cigarettes has the potential to be a risk factor for cardiovascular disorders in young adults.